2009
DOI: 10.1002/elan.200804548
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Hydrogel Layers on Microdisk Electrode Arrays: Cyclic Voltammetry Experiments and Simulations

Abstract: Poly(hydroxyethylmethacrylate)-based hydrogel membranes were applied to microfabricated, microdisk electrode arrays (MDEAs) of 50 mm (5184 disks), 100 mm (1296 disks) and 250 mm (207 disks) (d/r ¼ 4; A ¼ 0.1 cm 2 ) and studied by cyclic voltammetry (CV) in 1.0 mM ferrocene monocarboxylic acid (FcCO 2 H). The membrane produced an order of magnitude decrease in current densities and a shift to quasi reversibility due to a decrease in the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…The corresponding hydrogel diffusivity is consistent with previous observations of reduced diffusivity of redox anions within hydrogels when compared with transport within buffer (Boztas and Guiseppi-Elie 2009). Boztas and Guiseppi-Elie have shown that the redox active anion, ferrocene monocarboxylic acid (FcCOOH), has an effective diffusivity, D eff ¼ 1:13 Â 10 À8 cm 2 s À1 with n= 0.482, in a 3 M% TEGDA cross-linked p(HEMA)-based hydrogel and that it is approximately two orders of magnitude lower than that of the diffusivity observed in buffer solution D eff ¼ 4:51À ð 5:73 Â 10 À6 cm 2 s À1 Þ (Justin et al 2009a). However, the calculated diffusivity is in this case 10-fold lower than expected when compared to FcCOOH within a similar hydrogel.…”
Section: Electrical Impedance Of Hydrogel-coated Imesmentioning
confidence: 98%
“…The corresponding hydrogel diffusivity is consistent with previous observations of reduced diffusivity of redox anions within hydrogels when compared with transport within buffer (Boztas and Guiseppi-Elie 2009). Boztas and Guiseppi-Elie have shown that the redox active anion, ferrocene monocarboxylic acid (FcCOOH), has an effective diffusivity, D eff ¼ 1:13 Â 10 À8 cm 2 s À1 with n= 0.482, in a 3 M% TEGDA cross-linked p(HEMA)-based hydrogel and that it is approximately two orders of magnitude lower than that of the diffusivity observed in buffer solution D eff ¼ 4:51À ð 5:73 Â 10 À6 cm 2 s À1 Þ (Justin et al 2009a). However, the calculated diffusivity is in this case 10-fold lower than expected when compared to FcCOOH within a similar hydrogel.…”
Section: Electrical Impedance Of Hydrogel-coated Imesmentioning
confidence: 98%
“…Also, Guiseppi-Elie and coworkers recently pursued the use of a commercial micro-disc electrode arrays (ABTECH Scientific, Inc.) to probe hydrogels; their goal was to optimize the design parameters (geometry of the electrodes, thickness, composition of the hydrogel, and enzyme loading) to optimize the signal of an implantable amperometric biosensor [91,92]. The reader is referred to a recent review on electroconductive hydrogels to get in depth information on the subject [93].…”
Section: Principles Of Readout Platforms Supporting Bioresponsive Hydmentioning
confidence: 99%
“…More recently, the focus of electrochemical transduction involving hydrogels has been towards the miniaturization of conductimetric sensors using interdigitated electrodes to probe the conductivity of pH sensitive hydrogels [ 85 ], the use of blends of conducting polymer and redox hydrogels for more rugged glucose biosensors [ 86 ], and the fabrication of hydrogel coated ISFETs (ion sensitive field effect transistors) for the sensing of nucleotides, or monosacharides [ 87 , 88 ], and the formation of arrays of electrochemical sensors to probe multiple analytes using small biological samples [ 89 , 90 ]. Also, Guiseppi-Elie and coworkers recently pursued the use of a commercial micro-disc electrode arrays (ABTECH Scientific, Inc.) to probe hydrogels; their goal was to optimize the design parameters (geometry of the electrodes, thickness, composition of the hydrogel, and enzyme loading) to optimize the signal of an implantable amperometric biosensor [ 91 , 92 ]. The reader is referred to a recent review on electroconductive hydrogels to get in depth information on the subject [ 93 ].…”
Section: Principles Of Readout Platforms Supporting Bioresponsive Hydmentioning
confidence: 99%
“…The apparent diffusion coefficient, D appt , of ferrocene monocarboxylic acid (FcCO 2 H) through a base hydrogel has previously been determined. 36 It was shown in this study that with the application of a hydrogel to the surface of an MDEA chip, a decrease in the peak current response, as well as a decrease in the gradient of the Randles-Sevcik-like plot (Ip vs υ 1/2 ) occurs. From the gradients of the unmodified and hydrogelmodified chips, the diffusion coefficients can be calculated.…”
Section: Cyclic Voltammetry (Cv)mentioning
confidence: 68%